MEDICAL GEOGRAPHY : ITS ROLE IN DISEASE CONTROL AND HEALrn DEVELOPMENT IN AFRICA WITH PARTICULAR REFERENCE TO ETHIOPIA - Kloos, Helmut (The Ethiopian Journal of Health Development, 2017)
ABSTRACT This paper attempts to review selected medical geographical studies with objective of providing an overview of the sub field to geography and suggesting possible areas of collaboration with epidemiologists and public health officials in disease control programmes in Africa, particularly Ethiopia. A combination of: (1) complimentarity between medical geography and epidemiology; (2) the appropriateness of geography in analysing man-environment interactions; (3) the broad range of topics in disease ecology and health care delivery and utilization covered by medical geographers; (4) the need to evaluate aspects of the physical and socioeconomic environment in socialist Ethiopia for planning purposes and; (5) existence of viable programmes in medical geography in other African countries warrant consideration of this applied discipline in collaborative and interdisciplinary disease control programmes in Ethiopia.